Optical Nonlinearities and Thermal Diffusivity of Ag and Au Nanofluids - Shahriari, Esmaeil (2011)
In this study, nonlinear refractive index and nonlinear absorption of Ag nanometal polyvinylpyrrolidone (PVP), Au/PVP, and Au in polyvinyl alcohol (PVA) prepared by γ-radiation method were investigated using a single beam Z-scan technique. We measured the nonlinear refraction coefficient of silver nanofluid in concentrations ranging from 1.170×10 -3 to 5.885×10-3 M and in sizes ranging from 17.8 to 64.1 nm. We found the nonlinear refractive index is in the range of -4.18×10-8 to -9.57×10-8 cm2/W. This nonlinear effect increases as the concentration increases. A nonlinear relationship was obtained between nonlinear refractive index and particle size. The nonlinear absorption coefficient of Ag nanofluid at concentration of 4.71×10-3 M and three different sizes obtained to be 5.8×10-3, 4.5×10-3 and 3.2×10-3 cm/W. The results show that the particle size gives a significant effect to the nonlinear absorption coefficient. Nonlinear refractive index and nonlinear absorption of Au nanoparticle suspended in PVA solution at the range of concentration 1.471×10-4 to 7.063×10-4 M corresponding to particle size ranging from 7.0 to 58.0 nm was measured by using Z-scan technique. The Au nanofluid shows a good third-order nonlinear response. The sign of nonlinear refractive index is negative and the magnitude is in the range of -3.4×10-8 to -2.4×10-7 cm2/W. This nonlinear effect is found to increase with the increasing of particle sizes. These results show that the Au/PVA nanofluid give significant values of nonlinear refractive index, thus it could be a good candidate for optical devices. The nonlinear optical characteristic of Au nanoparticle suspended in PVP solution at the range of concentration 2.354×10-4 to 2.354×10-3 M corresponding to particle size of 4.0 to 48.2 nm was also studied by using Z-scan technique. The nonlinear refractive index value is in the range of -4.34×10-8 to -1.06×10-6 cm2/W. The nonlinear refractive index was found to increase with the increasing of concentration and particle sizes. All samples show the self-defocusing phenomenon. A dual beam mode-mismatched thermal lens method was employed to investigate the dependence of thermal diffusivity of Ag/PVP, Au/PVA, and Au/PVP nanofluids on nanoparticles sizes and concentration. Thermal diffusivity of Ag/PVP nanofluids at concentration range of 1.170×10-3 to 5.885 ×10-3 M with particle size from 17.8 to 64.1 nm was found to be in the range of 1.22×10-3 to 2.87×10-3 cm2/s. We found that thermal diffusivity of Ag/PVP nonlinearly increased with the increasing particle sizes and linearly increased with increasing the concentration of nanoparticles. Thermal diffusivity of Au/PVA nanofluids in the range of concentration 1.471×10-4 to 5.886×10-4 M and particle size ranging 7.0 to 41.2 nm was also measured and the values was ranging from 1.40×10-3 to 3.49×10-3 cm2/s. The thermal diffusivity increased systematically with concentration as increasing the doses. However, thermal diffusivity as a function of particle size increased unsystematically with increasing the irradiation dose. Thermal diffusivity of Au/PVP at two different concentrations, 4.708×10-4 M (particle size ranging from13.0-40.3 nm) and 5.886×10-4 M (particle size ranging from 15.5-48.2 nm) has been measured and the value varied from 3.04×10-3 to 4.84×10-3 cm2/s. In this case, the results show that thermal diffusivity of Au/PVP nanofluids increases with increasing the particle size.